Effectiveness of Coping Mechanisms in Stress Management: Perception from Shanker Dev Campus Students (NPRC Journal of Multidisciplinary Research, 2024)
This study explores the impact of stress on college students and the strategies to manage those stress. Stress is a universal element and persons from nearly every walk of life have to face it. Using a cross-sectional, descriptive quantitative research design, data were collected from 161 students from Shanker Dev Campus through structured questionnaire. All participants were enrolled in a business program. This study aims to evaluate the coping mechanism to manage stress used by students and also examine how stress effect different genders. The findings indicated no significant gender differences in coping mechanisms. However, coping mechanisms were found to be significant predictors of stress, with higher levels of constructive coping mechanisms associated with lower stress levels. These findings highlight the importance of effective coping strategies in managing stress and promoting mental well-being. This study fills a vital gap by focusing on the Shanker Dev Campus, bringing fresh insights into the specific consequences of stress on academic performance as well as well-being of students.